The Stress Management and Mental Literacy Trends of Health Science Student on Mental Health in Makassar - Sri Wahyu; Nurmiati Muchlis; Ilmianti Ilmianti3 (UMI Medical Journal, 2026)
Background: There are more than 40% who experience depression in adolescents but go undetected and untreated. The incidence of mental emotional disorders is increasing from year to year. The Prevalence of mental emotional disorders in Indonesia reached 6% in 2013 and increased to 9.8% in 2018. Riskesda data in 2018 stated that the number of cases of mental emotional disorders in South Sulawesi Province reached 10% in 2013 and increased to 13%. Objective: The aim of this study was to examine the association between stress management strategies (Problem-Focused Coping, Emotion-Focused Coping, and Maladaptive Coping) and academic stress with mental health among health science students in Makassar City. Methods: This research is quantitative research with a cross-sectional study approach. The research will start from September-November 2024. Data collection with proportional random sampling. The research was conducted in Makassar City at Hasanuddin University and Muslim Indonesia University) on health science students (Faculty of Medicine, Dentistry, Pharmacy, Public Health, Nursing. Data analysis using regression test between independent variables and dependent variables. Results: Among 121 health science students, Problem-Focused Coping, Emotion-Focused Coping, academic stress, and Maladaptive Coping were significantly associated with mental health (p < 0.05). Higher maladaptive coping scores were significantly associated with poorer mental health (B = −0.822; p = 0.003). Conclusion: Problem-Focused Coping, Emotion-Focused Coping, academic stress, and Maladaptive Coping were significantly associated with mental health among health science students in Makassar. Higher maladaptive coping was associated with poorer mental health. Universities should strengthen mental health promotion programs and encourage adaptive coping strategies to improve students' psychological well-being.